2018
DOI: 10.1007/s00253-018-9556-6
|View full text |Cite
|
Sign up to set email alerts
|

Plant health: feedback effect of root exudates-rhizobiome interactions

Abstract: The well-being of the microbial community that densely populates the rhizosphere is aided by a plant’s root exudates. Maintaining a plant’s health is a key factor in its continued existence. As minute as rhizospheric microbes are, their importance in plant growth cannot be overemphasized. They depend on plants for nutrients and other necessary requirements. The relationship between the rhizosphere-microbiome (rhizobiome) and plant hosts can be beneficial, non-effectual, or pathogenic depending on the microbes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
144
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 324 publications
(168 citation statements)
references
References 121 publications
0
144
0
7
Order By: Relevance
“…Thus, LCOs are crucial signaling molecules within the rhizosphere, which stimulates plant growth enhancement and could have an impact on plant nutrition via modification of the root structure [165]. The effect of LCOs on nutrient uptake enhancement in plants was reported in Medicago truncalata by Oláh et al [166], who observed an improvement in the number of lateral roots of the plant when LCOs were applied [167]. In the same way, a positive improvement in the root architecture of Arabidopsis thaliana was observed when plants were treated with LCOs from Bradyrhizobium japonicum.…”
Section: The Beneficial Effects Of Pgpr In Mineral Nutrient Uptake Inmentioning
confidence: 97%
See 1 more Smart Citation
“…Thus, LCOs are crucial signaling molecules within the rhizosphere, which stimulates plant growth enhancement and could have an impact on plant nutrition via modification of the root structure [165]. The effect of LCOs on nutrient uptake enhancement in plants was reported in Medicago truncalata by Oláh et al [166], who observed an improvement in the number of lateral roots of the plant when LCOs were applied [167]. In the same way, a positive improvement in the root architecture of Arabidopsis thaliana was observed when plants were treated with LCOs from Bradyrhizobium japonicum.…”
Section: The Beneficial Effects Of Pgpr In Mineral Nutrient Uptake Inmentioning
confidence: 97%
“…In the same way, a positive improvement in the root architecture of Arabidopsis thaliana was observed when plants were treated with LCOs from Bradyrhizobium japonicum. This resulted in an increase in the root surface area, the number of root tips, as well as the root lengths of A. thaliana treated plants [167,168].…”
Section: The Beneficial Effects Of Pgpr In Mineral Nutrient Uptake Inmentioning
confidence: 99%
“…A more robust and developed root system was observed in the bacteria-treated plants. Stimulation of root growth and effective root area for enhanced water and nutrient uptake is a very important stress management tool because a healthy and proliferated root system helps the plant maintain optimal growth and development under stress conditions (Olanrewaju et al, 2019;Mendes et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Plant root exudates are composed of a great variety of primary and secondary metabolites, including low-molecular weight compounds such as sugars, amino acids and organic acids, as well as high-molecular weight molecules such as mucilage and proteins (Bais et al 2006;Oburger and Jones 2018). The different molecules present in root exudates can mediate both positive and negative interactions in the rhizosphere (Huang et al 2014;Olanrewaju et al 2019). Focusing on the former, the symbiosis established between plants of the Leguminosae family and a group of alpha-proteobacteria named rhizobium has been widely studied.…”
Section: Introductionmentioning
confidence: 99%